WSNs based Oil Well Health Monitoring and Control Using ARM9 Processor - Dhatri, B.Siri; Rao, Y.Chalapathi; Rani, Dr.Ch.Santhi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The existing oil pumping system is a high power consuming process and has incapabilitys of CPUs structural health monitoring. Due to the environmental conditions and remote locations of oil and gas sites, it is expensive to physically visit assets for maintenance and repair. As the demand for oil and gas increases, reducing operating and maintenance costs and increasing reliability, this paper develops a sensor network based monitoring and control system, and improves the level of oil field security, enhance the security checking, and strengthen the management of digitalization and information. The system mainly consists of various sensors like temperature sensor, voltage sensor, current sensor, level sensor, PH sensor and gas sensor. Here we use gas sensor to detect the flammable gas which generally evolves from the oil wells. If any such detection occurs, automatically exhaust fan will switch on to pass away the particles. As like, in case if temperature level is high, cooling fan will trigger to reduce or maintain the particular temperature in the wells. With the help of current and potential transformer we can find out the fluctuations in the pumping section. If the level of oil varies from the indicated level it gives an alert message via voice recorder. To measure the level of humidity, we use PH sensor. All the sensors data is transmitted and monitored in PC using ARM processor. Also we can communicate this sensor data to other PCs using Zigbee technology.